Social sustainability in construction projects: Perception versus reality and the gap-filling strategies - Kordi, Nurul Elma; Belayutham, Sheila; Ibrahim, Che Khairil Izam Che (Frontiers in Built Environment, 2022)
Past studies have recommended integrating social sustainability in the construction project to benefit a larger group of stakeholders. However, deeper insight into integrating social sustainability practices in the project remains elusive. Therefore, this study intends to address the knowledge gap by exploring the practices and perspectives of social sustainability in a construction project. The study first verified and confirmed the applicability of the social sustainability attributes adopted from the literature through structured face-to-face interviews with 15 practitioners. The practitioners have unanimously agreed that the social sustainability attributes could be categorized into nine 9) main components, namely: 1) safety and health; 2) impact assessment; 3) employment; 4) stakeholder involvement; 5) satisfaction; 6) quality education; 7) social procurement; 8) design protection/belonging; and 9) human right along with the 20 sub-attributes. The practitioners have further ranked the importance of the attributes based on real practices (experience) in their project and their professional opinion (perception). The greatest gap between the perception and practices was attributed to stakeholder involvement, indicating the need for additional effort to proactively engage stakeholders throughout the construction process. Further investigation through the gap and quadrant analyses highlighted that the education and training attribute requires immediate attention to ensure social sustainability could be practiced due to its perceived importance. This study has two major contributions: 1) provided a holistic view of the real practices against the perceived importance of social sustainability in construction projects; 2) established the gap between perception and practices of social sustainability, subsequently highlighting the strategic way forward to narrow the gap.